2017
DOI: 10.1161/atvbaha.116.308620
|View full text |Cite
|
Sign up to set email alerts
|

EphrinB2 Activation Enhances Vascular Repair Mechanisms and Reduces Brain Swelling After Mild Cerebral Ischemia

Abstract: Objective— Cerebral edema caused by the disruption of the blood–brain barrier is a major complication after stroke. Therefore, strategies to accelerate and enhance neurovascular recovery after stroke are of prime interest. Our main aim was to study the role of ephrinB2/EphB4 signaling in mediating the vascular repair and in blood–brain barrier restoration after mild cerebral ischemia occlusion/reperfusion. Approach and Results— Here, we show that the gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
35
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 53 publications
5
35
0
1
Order By: Relevance
“…For example, viral overexpression of the positive guidance molecule Netrin1 promoted angiogenesis and long-term neurological recovery in a mouse model of transient focal ischemia (46). Also, activation of the guidance molecule ephrinB2 enhanced neurovascular repair and pericyte recruitment after brain ischemia (47). On the other hand, inhibition of the repulsive axonal guidance molecule Semaphorin 4D reduced BBB permeability as well as infarct volume and improved neurologic performance of rats after transient middle cerebral artery occlusion (48).…”
Section: Discussionmentioning
confidence: 99%
“…For example, viral overexpression of the positive guidance molecule Netrin1 promoted angiogenesis and long-term neurological recovery in a mouse model of transient focal ischemia (46). Also, activation of the guidance molecule ephrinB2 enhanced neurovascular repair and pericyte recruitment after brain ischemia (47). On the other hand, inhibition of the repulsive axonal guidance molecule Semaphorin 4D reduced BBB permeability as well as infarct volume and improved neurologic performance of rats after transient middle cerebral artery occlusion (48).…”
Section: Discussionmentioning
confidence: 99%
“…The significant increase in perivascular pericytes in RGS5-KO mice not only resulted in higher pericyte coverage but also in improved vascular density and length. It has been shown that pericytes are important modulators of vascular stabilization (811). Our findings are supported by previous evidence in a tumor model demonstrating that loss of RGS5 results in vascular normalization due to pericyte maturation (40).…”
Section: Discussionmentioning
confidence: 99%
“…During the chronic phase of stroke, pericytes are essential to stabilize the remaining and newly formed blood vessels (8)(9)(10)(11), but vessel wall-derived pericytes have also been described to migrate into the injured parenchyma and contribute to scar-forming PDGFR-b + cells (4,5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations